Immune Escape-Related Gene NXT1 as a Potential Prognostic and Therapeutic Target in Hepatocellular Carcinoma - Guo, Jia; Tong, Xin; Liu, Songtao; Liu, Feng; Qu, Yachao; Li, Ren; Bao, Xuli (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatocellular carcinoma (HCC) constitutes approximately 85% of liver cancers. This study aimed to investigate the role of immune escape-related genes (IEGs) in HCC patients and analyze their relationship with prognosis and immunotherapy, thereby providing a reference for further clinical treatment. Materials and Methods: Datasets were collected from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus databases. Differential expression analysis was conducted to identify differentially expressed IEGs between normal and HCC tissues. Expression, survival, mutational, and immune profiles of a hub gene nuclear transport factor 2 like export factor 1 (NXT1) were evaluated. Validation of NXT1 expression in adjacent normal and HCC tissues was carried out using RT-qPCR and western blot assays. Next, CCK-8, wound healing, and transwell assays were conducted to evaluate the biological function of NXT1 in HCC cell lines. Results: Analysis of the TCGA-LIHC and GSE164359 datasets revealed that NXT1 was notably elevated in HCC tissues compared to adjacent normal tissues, a finding validated through RT-qPCR and western blot assays. Meanwhile, high levels of NXT1 were associ ated with an unfavorable prognosis of HCC patients. Mutational analysis indicated a higher incidence of TP53 mutations in the NXT1 high-expression group relative to the NXT1 low-expression group. HCC patients with high NXT1 expression demonstrated an increased proportion of M0 macrophages and regulatory T cells (Tregs) and a decreased proportion of M1 macrophages. Furthermore, deficiency of NXT1 significantly suppressed HCC cell viability, migration, and invasion. Conclusion: Collectively, NXT1 may serve as a valuable prognostic marker and a potential therapeutic target for HCC. Cite this article as: Guo J, Tong X, Liu S, et al. Immune escape-related gene NXT1 as a potential prognostic and therapeutic target in hepatocellular carcinoma. Turk J Gastroenterol. Published online August 25, 2025. doi 10.5152/tjg.2025.24193.